Anti-Diabetic and Spermatogenic Activity of Cocculus Hirsutus (Linn.) Diels (Menispermaceae): Evaluation of the antidiabetic and spermatogenic activity of Cocculus Hirsutus (Menispermaceae) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Antidiabetic effect was observed with Cocculus hirsutus (Menispermaceae) when given its leaf extract. The study identified pharmacological evidence supporting the assertion of folklore that it is antidiabetic and decreases diabetes mellitus blood sugar.